A Sociolinguistic Approach to Language Levels in Social Interaction and Cultural Identity - Aminah, Mimin; Lustyantie, Ninuk; Chaeruman, Uwes Anis (Newinera Publisher, 2025)
This study explores the application of a sociolinguistic approach to language variations in the context of social interaction and cultural identity, particularly in the teaching of reading. By employing a qualitative research methodology, the study examines how formal and informal language, idiomatic expressions, and culturally specific terms within texts influence students’ reading comprehension and cultural literacy. Data were collected through interviews and discourse analysis involving students and educators engaged in reading instruction, with diverse texts such as literary works, folk tales, and non-formal narratives serving as primary materials. Findings indicate that students’ awareness of language variations significantly enhances their ability to decode contextual and cultural nuances, enabling deeper engagement with texts. Students who recognized the implications of linguistic choices—such as the use of formal versus informal registers—were better equipped to analyze character interactions, social dynamics, and embedded cultural values. Challenges emerged when students encountered idiomatic or culturally specific expressions, but these were mitigated through contextual analysis, consultation with external resources, and guided instruction. This study highlights the transformative potential of integrating sociolinguistic principles into reading pedagogy. It underscores the importance of fostering students’ critical literacy skills by exposing them to diverse linguistic styles and encouraging discussions on how language reflects social and cultural identities. The findings suggest that such approaches not only enhance reading comprehension but also promote cultural awareness and sensitivity, preparing students to navigate the complexities of a linguistically and culturally diverse world.